Pengaruh kepemimpinan kepala sekolah, kompensasi dan motivasi kerja terhadap kepuasan kerja guru MA Ma’arif NU Se-Kabupaten Purworejo - Fatmawati, Maratin; Khodijah, Khodijah (Indonesian Journal of Educational Management and Leadership, 2024)
Purpose − The research objectives include: (1) Knowing the influence of principals' leadership, compensation and work motivation on job satisfaction of teachers at MA Maarif NU in Purworejo District; (2) Knowing the influence of the principal's leadership on the job satisfaction of MA Maarif NU teachers in Purworejo Regency; (3) Knowing the effect of compensation on job satisfaction of teachers at MA Maarif NU in Purworejo District; and (4) Knowing the effect of work motivation on job satisfaction of teachers at MA Maarif NU in Purworejo Regency. Method − This type of research was quantitative research. The variables in this study were principal leadership, compensation, work motivation and teacher job satisfaction. The population of this study were all teachers who taught at MA Maarif NU in the Purworejo Regency area, which amounted to 122 people. This research was census research, so that the entire study population was teachers who teach at MA Maarif NU in the area of Purworejo Regency, amounting to 122 people. The total number of teachers was relatively small, making it easier for researchers to distribute questionnaires to all existing teachers. The data collection technique uses a questionnaire. The analysis used was multiple linear regression analysis. Findings − Based on the results of data analysis, conclusions were obtained: (1) Principal leadership, compensation and work motivation have a very significant positive effect on the job satisfaction of MA Maarif NU teachers in Purworejo Regency with amounted 42,4%. Positive and very significant means that the better the headmaster's leadership, compensation and work motivation, the teacher's job satisfaction will also be good, on the contrary if the headmaster's leadership gets worse, compensation and work motivation, then the teacher's job satisfaction will also be bad. (2) Principal leadership has a very significant positive effect on the job satisfaction of MA Maarif NU teachers in Purworejo District with amounted 17,0%. (3) Compensation has a very significant positive effect on the job satisfaction of MA Maarif NU teachers in Purworejo Regency with amounted 12,5%. (4) Work motivation has a very significant positive effect on the job satisfaction of MA Maarif NU teachers in Purworejo Regency with amounted 12,9%.